APPLICATION OF INDUCTIVE APPROACH TO IMPROVE MATHEMATICAL COMMUNICATION CAPABILITIES AND STUDENT SELF EFFICACY JUNIOR HIGH SCHOOL - Rifka Nadia; Euis Eti Rohaeti; Kustiana Kustiana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
Background of this research is still low ability of communication of mathematics and self efficacy of first middle school student. The purpose of this study is to improve the ability of mathematical communication and self efficacy of junior high school students whose learning using inductive approach in comparison with using ordinary learning in review of the student's early mathematical ability. The research method that is taken is quasi experiment. Data collection techniques in this study using quantitative techniques in the form of pretest, postes and n-gain of mathematical communication skills and self efficacy. The result of the research is that there is a difference in the improvement of mathematical communication ability of junior high school students whose learning using inductive approach with the learning using conventional approach and, there is no difference of self efficacy of junior high school students whose learning using inductive approach with the learning using conventional approach. Based on the results obtained then the inductive approach can be used as an alternative to improve the ability of mathematical communication and less suitable for self efficacy.